Developments in the field of removable anchors - Rebhan, M. J.; Marte, R.; Tschuchnigg, F.; Eder, A. S.; Fuschelberger, H.; Meyerhans, B. (IOP conference series. Earth and environmental science, 2021)
The design of inner-city building pits is a challenging task in geotechnical engineering. Due to rising property prices and the limited vacant plots in urban areas, the installation of building pit support measures is often constrained. Besides rigid systems, struts or anchors are often used to support such building pits. On the one hand, this support is required to come up with an economical design and on the other hand, it is necessary to keep the deformations of adjacent structures within certain limits. In this paper a new approach for the design and the (de-)installation process of removeable anchors is presented. By using a non-explosive cracking agent, a fully removeable anchor has been developed. Laboratory test results have shown, that by filling a pre-installed injection tube with the non-explosive cracking agent, a partial destruction of the grout body and consequently a reduction of the bond along the cement body and the steel tendon can be achieved. As a result, an extraction of the steel tendon is possible.